Mental Health Impact Analysis and Work Environment on Employee Productivity Gen Z - Wahyudi, Eko (Review: Journal of Multidisciplinary in Social Sciences, 2025)
This study aims to analyze the impact of mental health, particularly burnout, and the work environment on the productivity of Generation Z employees. An unfavorable work environment, including conflicts between employees and pressure from the company, also contributes to the stress experienced. This research emphasizes the importance of creating a positive and supportive work environment, where relationships between employees and between employees and leaders are well established. By paying attention to mental health and creating a comfortable work environment, companies can increase employee morale and productivity. These findings show that attention to employee well-being is the key to increasing productivity and loyalty of Generation Z employees in an increasingly complex era.